Treatment with Exogenous Trypsin Expands In Vitro Cellular Tropism of the Avian Coronavirus Infectious Bronchitis Virus - Phoebe Stevenson-Leggett (Viruses, 2020)
The Gammacoronavirus infectious bronchitis virus (IBV) causes a highly contagious and economically important respiratory disease in poultry. In the laboratory, most IBV strains are restricted to replication in ex vivo organ cultures or in ovo and do not replicate in cell culture, making the study of their basic virology difficult. Entry of IBV into cells is facilitated by the large glycoprotein on the surface of the virion, the spike (S) protein, comprised of S1 and S2 subunits. Previous research showed that the S2′ cleavage site is responsible for the extended tropism of the IBV Beaudette strain. This study aims to investigate whether protease treatment can extend the tropism of other IBV strains. Here we demonstrate that the addition of exogenous trypsin during IBV propagation in cell culture results in significantly increased viral titres. Using a panel of IBV strains, exhibiting varied tropisms, the effects of spike cleavage on entry and replication were assessed by serial passage cell culture in the presence of trypsin. Replication could be maintained over serial passages, indicating that the addition of exogenous protease is sufficient to overcome the barrier to infection. Mutations were identified in both S1 and S2 subunits following serial passage in cell culture. This work provides a proof of concept that exogenous proteases can remove the barrier to IBV replication in otherwise non-permissive cells, providing a platform for further study of elusive field strains and enabling sustainable vaccine production in vitro.